Ruch misyjny wśród młodzieży akademickiej w okresie międzywojennym w ówczesnej refleksji teologicznej - Mich, Katarzyna Anna (Annales Missiologici Posnanienses, 2023)
On the 90th anniversary of the creation of the Academic Missionary Movement in Poland, an attempt is made to analyze the theological reflection undertaken then with regard to the missionary commitment of students, which justified the involvement of young people in the mission and established its principles and scope of action.